2003
DOI: 10.1046/j.1473-6861.2003.00038.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving pain management through interprofessional education: evaluation of a pilot project

Abstract: A collaborative project between a district hospital and a local university resulted in a senior lecturer being seconded 2 days per week to facilitate the continued improvement in pain management. The rationale for this collaboration was to explore the utilization of innovative teaching methods to deliver education in practice and to develop further research in relation to pain management. An interprofessional pain steering group (IPSG) was established with representation from several services (acute pain, chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 38 publications
(39 reference statements)
0
22
0
1
Order By: Relevance
“…One reason for this may be found in the education of the health professionals in whose care these patients lie. It is a multidimensional phenomenon that cuts across professional boundaries, pharmacists, nurses, psychologists, occupational therapists, doctors and physiotherapists all having an input into its management (Carr et al, 2003). This may be because effective pain management can be complex, requiring approaches that exceed the expertise of one profession.…”
Section: Introductionmentioning
confidence: 99%
“…One reason for this may be found in the education of the health professionals in whose care these patients lie. It is a multidimensional phenomenon that cuts across professional boundaries, pharmacists, nurses, psychologists, occupational therapists, doctors and physiotherapists all having an input into its management (Carr et al, 2003). This may be because effective pain management can be complex, requiring approaches that exceed the expertise of one profession.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, these data indicated that participants felt the course had provided them with the skills and ability to act as leading figures within their respective organizations for interprofessional practice when working with the manifestation and consequences of violence, as well as to work effectively as collaborators with colleagues based in other disciplines, professions and agencies. Although no published research could be located reporting the effects of interprofessional education on staff working with the survivors of violence, a broader search of the literature did indicate that this study's findings related to the early gains in attitudes and knowledge reported by other authors based in the interprofessional education field (e.g., Carr et al, 2003;Kilminster et al, 2004).…”
Section: Discussionmentioning
confidence: 76%
“…Persistent pain leads to changes in the nervous system, creating a vicious cycle that prolongs and worsens pain and causes longer hospitalization, longer recovery period and increased medical costs (Davidhizar & Bartlett, 2000). Regardless of pain's origin, it is a multidimensional phenomenon beyond professional boundaries, for doctors, nurses, physiotherapists and other professions all have input into its management (Carr et al, 2003). It seems the management of such complex phenomenon, particularly in post registration continuing education, is a real concern which needs to be scrutinized.…”
Section: Introductionmentioning
confidence: 99%